Internal and external policy of the byzantine empire during the reign of emperor justinian - touil, imad (Journal of Social Sciences and Humanities, 2026)
The Roman Empire extended the land east and west, including all of Europe, Africa and Asia, thus controlling all of the Mediterranean regions until it was named d 'after its name "The sea of rome". This great expansion led to its division into two parts, the east and the west (Eastern Rome is its capital, Byzantium and Western Rome. Its capital is Rome), the division caused great weakness in Western Rome, which led to its fall to the Germanic tribes (the Goths) in the late 5th century AD, but Roman civilization continued to be represented in eastern Rome (the Byzantine Empire and its capital Byzantium), which would continue to impose his control and his power at sea The aim of the research is to study the personality of the Byzantine emperor Justinian, and to research the internal and external policies carried out by the latter in Africa, Europe and Asia, and which sought to embody the principle of the legitimacy of the Eastern Roman heritage to the western regions of Rome lost in the hands of the Germanic tribes. Analytical narrative compared in the study of various historical events which occurred in the ancient world at the beginning of the sixth century AD and the transformations which took place in the various ancient empires throughout Africa, Asia and the Europe and the various wars that arose in the Mediterranean, which were the main cause of the Byzantine Empire due to the policies of Emperor Justinian and the wars he fought to restore the glories of the old Roman Empire, and Emperor Justinian was able to organize the Byzantine Empire internally and externally and give it prestige by reorganizing the Mediterranean Sea, absent from the central administration and neighboring controlled provinces, and establishing a strong and solid empire that resisted to the Persian tide in the East and lasts for several centuries with the same prestige after the death of Emperor Justinian.